2016
DOI: 10.3390/ijerph13111131
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Is an Important Modifiable Risk Factor in Sickle Cell Disease: A Review of the Current Literature and Areas for Future Research

Abstract: Sickle cell disease (SCD) is an autosomal recessive hemoglobinopathy that causes significant morbidity and mortality related to chronic hemolytic anemia, vaso-occlusion, and resultant end-organ damage. Tobacco smoke exposure (TSE) through secondhand smoke exposure in people with SCD of all ages and through primary smoking in adolescents and adults is associated with significantly increased morbidity, with increased rates of emergency department visits and hospitalizations for painful vaso-occlusive crises and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
(119 reference statements)
0
8
0
Order By: Relevance
“…Cigarette smoking increases blood Hb levels (63,64), suggesting protection from anemia; however, CS may affect the incidence as well as the diagnosis of anemia by negatively affecting hematopoiesis and inducing polycythemia (65). Smoking may increase the risk of anemia during pregnancy, may worsen iron accumulation, and may exacerbate preexisting iron-related conditions such as sickle cell disease (60,66,67). Smokers also have lower serum ceruloplasmin levels than nonsmokers, suggesting impaired protection from reactive Fe 21 (68).…”
Section: Cigarette Smoking Alters Iron Homeostasis In the Lungmentioning
confidence: 99%
“…Cigarette smoking increases blood Hb levels (63,64), suggesting protection from anemia; however, CS may affect the incidence as well as the diagnosis of anemia by negatively affecting hematopoiesis and inducing polycythemia (65). Smoking may increase the risk of anemia during pregnancy, may worsen iron accumulation, and may exacerbate preexisting iron-related conditions such as sickle cell disease (60,66,67). Smokers also have lower serum ceruloplasmin levels than nonsmokers, suggesting impaired protection from reactive Fe 21 (68).…”
Section: Cigarette Smoking Alters Iron Homeostasis In the Lungmentioning
confidence: 99%
“…It is estimated that around 50 smokers can contribute to the death of one non-smoker individual who is exposed to SHS [ 3 ]. Meanwhile, passive smoking has significant contributions to the incidence of sickle cell disease [ 4 ]. In children, passive smoking has hazardous effects on lung and immune functions, and it can increase the severity of cystic fibrosis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent pediatric study found RSV was commonly associated with ACS in children, and disease severity was comparable to influenza 11 . Interestingly, multiple risk factors for severe RSV disease in the general pediatric population overlap with risk factors for ACS in children with SCD, including peak incidence in children <5 years of age, 12,13 underlying asthma diagnoses, 14,15 exposure to second‐hand smoke, 16,17 and winter seasonality 13,18 . Thus, children with SCD appear to have risk factors for RSV disease, although they are not currently considered a high‐risk group for whom palivizumab prophylaxis is recommended.…”
Section: Introductionmentioning
confidence: 99%